2020
DOI: 10.3390/plants9091231
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Increased N Deposition on Leaf Functional Traits of Four Contrasting Tree Species in Northeast China

Abstract: Northeast China is persistently affected by heavy nitrogen (N) deposition. Studying the induced variation in leaf traits is pivotal to develop an understanding of the adaptive plasticity of affected species. This study thus assesses effects of increased N deposition on leaf morphological and anatomical traits and their correlation among and with biomass allocation patterns. A factorial experiment was conducted utilizing seedlings of two gymnosperms (Larix gmelinii, Pinus koraiensis) and two angiosperms (Fraxin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 73 publications
4
11
0
Order By: Relevance
“…A pronounced C limitation under L− might thus explain the lack of leaf trait acclimation (besides LMF) to nitrogen addition. Under L+ conditions, our results were partially in line with previous studies reporting a significantly decreased LMA [26] but contrasted others which reported an increase in the leaf area and/or no significant change in LMA [63,67] under increased N fertilization. However, plant traits in general, and leaf traits in specific, were known to change largely during ontogeny [66].…”
Section: Effects Of Shade and N Availability On Leaf Traitssupporting
confidence: 92%
See 3 more Smart Citations
“…A pronounced C limitation under L− might thus explain the lack of leaf trait acclimation (besides LMF) to nitrogen addition. Under L+ conditions, our results were partially in line with previous studies reporting a significantly decreased LMA [26] but contrasted others which reported an increase in the leaf area and/or no significant change in LMA [63,67] under increased N fertilization. However, plant traits in general, and leaf traits in specific, were known to change largely during ontogeny [66].…”
Section: Effects Of Shade and N Availability On Leaf Traitssupporting
confidence: 92%
“…These contrasting findings were related to the very low leaf densities discovered, which enabled both species to develop more and larger-sized leaves despite an increased leaf thickness. Previously, some studies indicated that LMA was either equally dependent on the variation of LT and LD [62], was strongly reliant on LT [26,45], or linked to LT and leaf volume per area (LVA) [63,64]. Our results indicated that the variation in LMA across the studied species depended strongly on LD, supporting the former findings.…”
Section: Effects Of Shade and N Availability On Leaf Traitssupporting
confidence: 86%
See 2 more Smart Citations
“…2a , compared with T1, the leaf thickness of T2 and T3 were significantly increased, and the difference reached a significant level ( p < 0.05) and an extremely significant level ( p < 0.01). Leaf thickness is generally considered as a valuable characteristic, which may be related to resource acquisition, water conservation and assimilation [ 41 ]. Leaf tissue thickness was positively correlated with leaf water use efficiency, and is also closely related to leaf water storage capacity [ 42 ].…”
Section: Resultsmentioning
confidence: 99%